Maternal control of suspensor programmed cell death via gibberellin signaling - Ce Shi (Nature Portfolio, 2019)
Plant embryos are connected to maternal tissue by a filamentous suspensor, analogous to an umbilical cord, but which is severed during early embryo development. Here, Shi et al. show that gibberellins can trigger suspensor cell death in tobacco via a DELLA protein that regulates expression of cell death factors.